ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KEMISKINAN DI PROVINSI SULAWESI UTARA TAHUN 2010-2019 (Analysis of the Influence of Economic Growth and Human Development Index on Poverty Level in North Sulawesi 2010 – 2019) - Christine Veronika Manoppo; Paulus A. Pangemanan; Olly E. H. Laoh (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the effect of economic growth and the human development index (HDI) on the poverty rate in North Sulawesi Province in 2010-2020 and 2010-2025 after obtaining predicted data based on the previous year's data. This research was conducted in the province of North Sulawesi. This research started from July 2020 to January 2021. This study used secondary data of economic growth, human development index and poverty rate of North Sulawesi Province in 2010-2020. The analytical tool used in this research was multiple linear regression analysis with the method of Ordinary Least Square (OLS) and forecasting using Trend Linear with the semi-average method. The results showed that for the period 2010-2020, simultaneously, economic growth and HDI had no effect on the poverty rate in North Sulawesi Province with a significant value of 0.059. The results of the regression showed that there was an insignificant effect of economic growth on the poverty level. The negative effect was 0.053 percent and a significant value of 0.545 means that economic growth has no significant effect. Meanwhile, HDI on poverty showed a significant effect. The negative effect was 0.282 percent. A significant value of 0.025 indicated  that HDI had a significant effect on the level of poverty. In the period of 2010-2025,  simultaneously, economic growth and HDI had  an effect on the poverty rate in North Sulawesi Province with a significant value of 0.004. The results of the regression showed that there was an insignificant effect of  economic growth on the poverty level. The negative effect was 0.053 percent, with a significant value of 0.437, meaning that economic growth had no significant effect. HDI had  a significant effect on poverty levels. The negative effect was 0.281 percent, with a significant value of 0.002 which means that HDI had a  significant effect  on the poverty level.